Book Scavenger - Bertman, Jennifer Chambliss (Square Fish : Henry Holt and Company, 2016)
After moving to San Francisco, home of Garrison Griswold, the creator of the hit online game Book Scavenger, twelve-year-old Emily becomes caught up in investigating an attack on Garrison while following the clues of his latest scavenger hunt.